The establishment of an early intervention programme using parent–infant psychotherapy in South America. Issue 2 (2nd September 2017) - Navarro, Javiera; Martínez, Mónica
ABSTRACT: This paper shares some clinical thoughts obtained during the first years of an Early Intervention Programme in the Faculty of Psychology of a South American University. It includes a brief review of literature which supports the relevance of early interventions and discusses some of the theoretical concepts which guided the clinical work which the authors describe. The paper concludes with reflections on one of the team's first cases.